Patterns of upper limb muscle activation in children with unilateral spastic cerebral palsy: Variability and detection of deviations. (November 2018) - Sarcher, Aurélie; Brochard, Sylvain; Hug, François; Letellier, Guy; Raison, Maxime; Perrouin-Verbe, Brigitte; Sangeux, Morgan; Gross, Raphaël
Abstract: Background: The aim of this study was two-fold: (1) to quantify the variability of upper limb electromyographic patterns during elbow movements in typically developing children and children with unilateral spastic cerebral palsy, and to compare different amplitude normalization methods; (2) to develop a method using this variability to detect (a) deviations in the patterns of a child with unilateral spastic cerebral palsy from the average patterns of typically developing children, and (b) changes after treatment to reduce muscle activation. Methods: Twelve typically developing children ([6.7–15.9yo]; mean 11.0 SD 3.0yo) and six children with unilateral spastic cerebral palsy ([7.9–17.4yo]; mean 12.4 SD 4.0yo) attended two sessions during which they performed elbow extension-flexion and pronation-supination movements. Surface electromyography of the biceps, triceps, brachioradialis, pronator teres, pronator quadratus, and brachialis muscles was recorded. The Likelihood method was used to estimate the inter-trial, inter-session, and inter-subject variability of the electromyography patterns for each time point in the movement cycle. Deviations in muscle patterns from the patterns of typically developing children and changes following treatment were evaluated in a case study of a child with cerebral palsy. Findings: Normalization of electromyographic amplitude by the mean peak yielded the lowest variability. The variability data were then used in the case study. This method detected higher levels of activation in specific muscles compared with typically developing children, and a reduction in muscle activation after botulinum toxin A injections. Interpretation: Upper limb surface electromyography pattern analysis can be used for clinical applications in children with cerebral palsy. Highlights: Three techniques of electromyography amplitude normalization are compared. Normalization using the mean peak value during dynamic trials is appropriate. Variability of upper limb electromyographic patterns is quantified in children. Inter-trial and inter-session variability are equivalent. Variability is similar between children with cerebral palsy and typical development.